Edutech For Sustainability: Digital Innovation In Social And Environmental Learning - Nurhayati Nurhayati; Weni Sarbaini; Atania Rosbina Br Bangun; Razid Ananda Siregar; Damenta Br Ginting (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze the effectiveness of digital innovation in EduTech platforms in improving elementary students' cognitive understanding and socio-environmental behavioral intention, comparing EduTech-based learning with conventional methods within an Education for Sustainable Development framework. Methodology: This study used a quantitative quasi-experimental Pretest-Posttest Control Group Design involving 50 fourth-grade students (25 experimental, 25 control) at UPTD SD Inpres Oelmasi, selected through cluster random sampling. Data were collected using validated comprehension tests and Likert-scale questionnaires, then analyzed using N-Gain scores, Shapiro-Wilk normality test, Levene's homogeneity test, Mann-Whitney U test, and rank-biserial correlation (effect size). Main Findings: Both groups showed improved post-test scores, but the experimental group using EduTech achieved a higher mean N-Gain than the control group. Shapiro-Wilk and Q-Q plot results indicated non-normal data distribution, so hypothesis testing used the Mann-Whitney U test (U = 169.5, p < .05), confirming a statistically significant difference favoring EduTech. The rank-biserial correlation (r = .445) indicated a moderate practical effect, demonstrating EduTech's meaningful contribution to students' understanding of social and environmental sustainability.. Novelty/Originality of this study: Unlike prior studies that mostly focus on general academic achievement or specific subjects, this study specifically evaluates EduTech's effectiveness in supporting integrated social and environmental sustainability learning at the elementary level. By empirically testing the Connectivism theory and TPACK framework together, it extends evidence on early-age digital pedagogy for Education for Sustainable Development and offers practical guidance for teachers implementing ESD-based digital learning strategies.